2014
DOI: 10.1021/jz5017729
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intermolecular Distance on Singlet Fission in a Series of TIPS Pentacene Compounds

Abstract: Singlet fission has attracted considerable interest for its potential application in organic photovoltaics. However, the underlying microscopic mechanism is not well understood and the molecular parameters that govern SF efficiency remain unclear. We herein study the primary exciton photogeneration and evolution in the thin film of a series of pentacene derivatives (TIPS-Pn and ADPD-Pn) using femtosecond transient absorption spectroscopy. With a favorable "long-edge on" packing motif, the singlet-excited slip-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
92
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 21 publications
11
92
0
1
Order By: Relevance
“…29 The pump beams and the probe beams originate from the same laser pulse at 800 nm (120 fs, 1 kHz) by using a 9 : 1 beam splitter. Thus, we can calculate the absorbance difference for these two probe beams to obtain the absorption spectra of the excited-state.…”
Section: Methodsmentioning
confidence: 99%
“…29 The pump beams and the probe beams originate from the same laser pulse at 800 nm (120 fs, 1 kHz) by using a 9 : 1 beam splitter. Thus, we can calculate the absorbance difference for these two probe beams to obtain the absorption spectra of the excited-state.…”
Section: Methodsmentioning
confidence: 99%
“…[35][36][37][38][39][40][41][42][43] In this case, a largely unexplored question is the relationship between SF process and SE migration. Several experiments 37,38,40 have observed that the SE delocalization can drive a rapid SF process in well-arranged molecular crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the same authors have demonstrated that the control of the structural arrangement in films boosts the field‐effect mobility to remarkable values of 11 cm 2 V −1 s −1 . In addition, this molecule has recently emerged as a paradigm to study singlet fission process in both solution and thin films, owing to its triplet quantum yield formation exceeding values of 100% . Finally, the sharp red emission at around 650 nm and the moderate photoluminescence quantum yields (PLQYs) when dispersed in a thin film with the electron‐transporting host tris(quinoline‐8‐olato)‐aluminum(III) (Alq 3 ) prompted Kafafi and Anthony groups to fabricate the first OLEDs based on trialkylsilylethynyl‐substitute pentacenes .…”
Section: Introductionmentioning
confidence: 99%